Amorphous and photoluminescent crystalline silicon carbide nanoparticles synthesized by laser ablation in liquids. (2022) - Shuaib, E.P.; Yogesh, Gaurav Kumar; Sastikumar, D.
Abstract: Amorphous and crystalline SiC nanoparticles were synthesized via laser ablation of SiC micro-sized powder in water and ethanol. X-ray and HRTM analysis showed the amorphous nature of SiC nanoparticles with an average particle size of 44 nm in water and crystalline 6H-SiC polytype nanoparticles with an average size of 18 nm in ethanol. The direct and indirect bandgap of SiC nanoparticles were determined from UV–visible absorption spectra. PL emission characteristics were studied and crystalline SiC nanoparticles exhibit tunable PL emission covering UV to the visible region.